2019
DOI: 10.1159/000499491
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Percutaneous Nephrolithotomy for Complex Staghorn Stones in Children

Abstract: Objectives: To evaluate the safety and efficacy of percutaneous mini-nephrolithotomy (mini-PCNL) in children with complex staghorn stones. Patients and Methods: We analyzed prospectively data of 28 children undergoing pediatric mini-PCNL during a period of 18 months. Stone complexity was defined according to the validated Guy’s stone score (GSS). Our patients were GSS III and IV. All PCNL procedures were performed in the prone position, under fluoroscopic guidance, and in the same standardized fashion with F12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…(1) e perioperative conditions of the two groups were statistically analyzed, including the length of operation, intraoperative blood loss, stone clearance rate, length of hospital stay, and degree of pain, and the degree of pain was assessed according to the VAS scale, with a total of 10 points, and the lower the score, the better. (2) e levels of renal function (blood urea nitrogen (BUN), serum creatinine (Scr), and cystatin (C) were measured before and 1 d after operation in both groups. (3) e levels of inflammatory factors (C-reactive protein (CRP), procalcitonin (PCT)) before surgery and 1 d after surgery were counted in both the groups.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) e perioperative conditions of the two groups were statistically analyzed, including the length of operation, intraoperative blood loss, stone clearance rate, length of hospital stay, and degree of pain, and the degree of pain was assessed according to the VAS scale, with a total of 10 points, and the lower the score, the better. (2) e levels of renal function (blood urea nitrogen (BUN), serum creatinine (Scr), and cystatin (C) were measured before and 1 d after operation in both groups. (3) e levels of inflammatory factors (C-reactive protein (CRP), procalcitonin (PCT)) before surgery and 1 d after surgery were counted in both the groups.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Complex kidney stones are mainly staghorn-shaped or multiple and large stones with a diameter of ≥2.5 cm. In general, stones are numerous, widely distributed, and difficult to remove, posing a great threat to the quality of life and physical and mental health of patients [ 1 , 2 ]. Therefore, timely, safe, and effective treatment for patients with complex kidney stones is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide prevalence, incidence, and composition of calculi vary and in Asia, 1-19.1% of the population suffers from urolithiasis [ 2 , 3 ]. With the advances of surgical technology, less invasive procedures such as percutaneous nephrolithotomy (PCNL) have gradually become a preferred therapy for urinary stones [ 4 , 5 ]. Since its introduction, a variety of alterations and improvements has been made to the procedure in order to achieve maximum stone clearance along with decreasing the morbidity in patients, postoperative analgesic requirement, and postoperative hospital stay [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On other hand, Kumsart et al [20], found a significant relationship between GSS and postoperative complications but not with SFR. Rashid et al [27] extended the application of GSS to grade the stone complexity in pediatric population in their study to evaluate the safety and efficacy of percutaneous mini-nephrolithotomy (mini-PCNL).…”
Section: Discussionmentioning
confidence: 99%